Plasma treatments and photonic nanostructures for shallow nitrogen vacancy centers in diamond - Radtke, Mariusz; Render, Lara; Nelz, Richard; Neu, Elke (Optical Materials Express, 2019)
We investigate the influence of plasma treatments, especially a 0V-bias, potentially low damage O2 plasma as well as a biased Ar/SF6/O2 plasma on shallow, negative nitrogen vacancy (NV-) centers. We ignite and sustain our 0V-bias plasma using purely inductive coupling. To this end, we pre-treat surfaces of high purity chemical vapor deposited single-crystal diamond (SCD). Subsequently, we create 10 nm deep NV- centers via implantation and annealing. Onto the annealed SCD surface, we fabricate nanopillar structures that efficiently waveguide the photoluminescence (PL) of shallow NV-. Characterizing single NV- inside these nanopillars, we find that the Ar/SF6/O2 plasma treatment quenches NV- PL even considering that the annealing and cleaning steps following ion implantation remove any surface termination. In contrast, for our 0V-bias as well as biased O2 plasma, we observe stable NV- PL and low background fluorescence from the photonic nanostructures.
CRIS-Team Scopus Importer:2023-03-27